Timing of vaccination after training: Immune response and side effects in athletes - Stenger, T.; Ledo, A.; Ziller, C.; Schub, D.; Schmidt, T.; Enders, M.; Gärtner, B. C.; Sester, M.; Meyer, T. (Medicine & Science in Sports & Exercise, 2020)
Objectives: Influenza vaccination was used to assess whether induction of immunity or side effects are influenced by the timing of the last training session before vaccination. Methods: Forty-five healthy athletes (36 male, 23 ± 8 yr, =5 training sessions per week, predominantly national competition level) were vaccinated with the tetravalent influenza vaccine; blood samples were collected immediately before and 1, 2, and 26 wk after vaccination. Athletes were randomly assigned to vaccination within 2 h after the last training session versus after 24-26 h. Influenza-specific T cells were quantified after stimulation with the vaccine based on intracellular cytokine staining. Antibodies (IgA, IgG, IgM) were quantified by enzyme-linked immunosorbent assay and neutralization assay. Participants documented resulting side effects and training restrictions using a standardized diary. Results: Both groups showed an increase in influenza-reactive CD4 T-cell levels, which peaked 1 wk after vaccination (fold changes to baseline; median (interquartile range), 3.7 (3.0-5.4; P < 0.001) in the 2-h group; 4.6 (2.8-7.4; P < 0.001) in the 26-h group) with no difference between groups (P = 0.52). Influenza-specific antibodies showed a significant increase after vaccination in both groups (at least 1.4-fold, each P < 0.001, no group differences; P = 0.24-0.97 for different antibody types). Only antibodies toward the Brisbane strain showed a trend toward significant differences in neutralization titers between groups (4-fold (2-17.8) in the 2-h group, 16-fold (4-32.9) in the 26-h group; P = 0.06), whereas other specificities did not differ (P = 0.16-0.72). No intergroup differences were found for side effects; no athlete reported a loss of training time due to the vaccination or its side effects. Conclusion: Infection prophylaxis in elite athletes by influenza vaccination seems to be effective and safe. Timing of vaccination after prior training does not seem to require specific constraints.